Uncertainty analysis in elastic and electrical properties of hydrocarbon reservoir: Pitfalls and propose solutions - Luluan, L. (European Association of Geoscientists and Engineers, EAGE, 2019)
For the last decades, the seismic amplitude is the main tool for hydrocarbon predictions. Although seismic data provides subtle information about the structure and geometry, the sensitivity to hydrocarbon fluids is still limited. This paper presents the uncertainties and sensitivity analysis of seismic amplitude and other common elastic properties in discriminating the hydrocarbon fluids. We found out that almost all elastic properties failed in discriminating low hydrocarbon saturation. We present the pitfalls and propose solutions by for hydrocarbon reservoir discrimination especially on low hydrocarbon reservoirs. Â© 2019 Asia Petroleum Geoscience Conference and Exhibition, APGCE 2019. All rights reserved.